Risk factors for chemotherapy‐induced peripheral neuropathy in patients receiving taxane‐ and platinum‐based chemotherapy. Issue 6 (7th May 2019) - Molassiotis, Alex; Cheng, Hui Lin; Leung, Kwun To; Li, Yu Chung; Wong, Kam Hung; Au, Joseph Siu Kie; Sundar, Raghav; Chan, Alexandre; Ng, Terrence Rong De; Suen, Lorna K. P.; Chan, Choi Wan; Yorke, Janelle; et al.
Abstract: Background: Chemotherapy‐induced peripheral neuropathy (CIPN) is a significant and difficult to manage side effect of neurotoxic chemotherapies. Several risk factors for CIPN have been identified to date, but inconsistencies and methodological limitations exist in past research. Also, a limited number of potential risk factors has been investigated in the past. Aim: The objective of this study was to assess the relative contribution of a wider range of risk factors in the development of CIPN. Methods: This analysis used the 6‐month data after starting chemotherapy from a larger prospective observational study on CIPN risk, prevalence, and quality of life. Patients were assessed at recruitment for possible CIPN risk factors, including prior history of neuropathies, current/past infectious diseases; neurotoxic medication history; personal and treatment characteristics; smoking history, alcohol use, and vegetable/fruit intake. Neuropathy was assessed at 6‐months after starting chemotherapy with the neuropathy (motor/sensory) items of the NCI‐CTCAE scale and the WHO criterion for neuropathy. Data on symptom burden were also collected. Results: Data were available from 255 patients from three cancer centers in Hong Kong, Singapore, and UK. The use of different scales did not always identify the same predictor variables. Key risk factors in multivariate regression models included older age (highest OR = 1.08, p  < 0.01 with the WHO scale), chemotherapy (platinum‐based chemotherapy had OR = 0.20–0.27 in developing CIPN compared to taxane‐based chemotherapy), history of neuropathy (for motor CIPN only, OR = 8.36, p  < 0.01), symptom burden (OR = 1.06, p  < 0.05), number of chemotherapy cycles received (OR = 1.19–1.24, p  < 0.01), and alcohol intake (OR = 0.32, p  < 0.05). In univariate analysis, the use of statins was implicated with CIPN ( p  = 0.03–0.04 with different assessments) and diabetes showed a trend ( p  = 0.09) in the development of CIPN. Conclusion: This study confirmed the CIPN risk related to certain variables and identified new ones. This knowledge can assist with treatment decisions and patient education. Abstract : Risk factors in the development of chemotherapy‐induced peripheral neuropathy.